86 Long-term outcome of critical aortic valve stenosis. (22nd November 2019) - Bonello, Bea; Carr, Michelle; Issitt, Richard; Hugues, Marina; Giardini, Alessandro; Iriart, Xavier; Tsang, Victor; Kostolny, Martin; Khambadkone, Sachin; Marek, Jan
Abstract : Background: Survival with critical aortic valve stenosis (CAS) can be successfully achieved in the short term. Long-term outcome however remains uncertain. We sought to study the long-term survival and reinterventions; exercise capacity and myocardial performance in a subgroup of long-term survivors. Methods: Retrospective over 40 years of all patients (n=96) requiring intervention for CAS. A subgroup (n=25) of long-term survivors underwent cardiopulmonary exercise test, echocardiography and magnetic resonance imaging. Results: Mean age at first intervention was 9±7.5 days. Early death occurred in 19 (19.8%) and overall reported death was 29 (32.9%). At 20 years, survival rate was 65.8% and freedom from reintervention was 24% (figure 1A and 1B ). Median age of our long-term survivors, median age was 15.7±6.4 years, 16(64%) had a Ross procedure and 3(12%) had a mechanical aortic valve. Sixteen patients were in NYHA I, 3 NYHA II, 6 NYHA III. Overall peak VO2 was mildly depressed (84.6±24% predicted; 32.1±8.2 ml/kg/min), normal in 9(45%), severely depressed in 6 (30%). Mean left ventricle (LV) ejection fraction was 65.5±11.22% and mean LV end-diastolic volume Z score was 0.02±1.4. Mean LV outflow tract Vmax was 2.27±1.17 m/s. Four patients (16%) had moderate aortic regurgitation. Mean right ventricular outflow gradient was 19.23±23.57 mmHg. Five patients (20%) had severe LV diastolic dysfunction on echocardiography and confirmed by invasive measurement. Severe diastolic dysfunction was not associated with an older age (p=0.15), small ventricular dimension (p=0.2) or residual obstruction (p=0.39) but was associated with the presence of endocardial fibroelastosis (p=0.00014). Conclusions: After an early mortality, long-term survival of patients with critical aortic stenosis is good at the expense of a high rate of reinterventions. Despite a good clinical status, myocardial assessment revealed a high rate of LV diastolic dysfunction that could be a marker of irreversible intrinsic myocardial damage.